Topologies and control methods for protection of DC electrical system in aircraft - Marwaha, Mridul (Nanyang Technological University, 2023)
Conventional aircraft are evolving towards more-electric aircraft, replacing the mechanical, pneumatic, and hydraulic subsystems with their electrical counterparts. More-electric aircraft provide many advantages such as high efficiency, extended control, less maintenance requirement, and fuel saving. Recent studies have shown that the adoption of a dc grid in these electrical systems further improves the overall efficiency and performance. However, fault currents in dc grids have no zero crossings, making fault isolation highly challenging. In ac grids, mechanical circuit breakers (MeCBs) are the most commonly used fault isolation devices. However, there are several limitations of MeCBs in dc grids such as slow response time, additional auxiliary circuit requirement, and limited dc fault current breaking capability. To overcome these limitations, solid-state power controllers/ solid-state circuit breakers (SSPCs/ SSCBs) are emerging as a promising technology for protection of dc electrical systems in aircraft. This thesis is mainly focused on these SSPCs/ SSCBs. The capacitors associated with the power electronic converters are initially at zero potential. Direct connection of a dc source and these capacitors, results in very high peak current and voltage overshoot, which can cause high stress on the semiconductor devices, capacitors, and current feeding components. One of the main challenges of SSPCs/ SSCBs is to smoothen the inrush current. The first part of the contribution of the thesis is focused on precharging. Constant current precharging control strategy is proposed in this thesis, which regulates the semiconductor device current by varying the gate-source voltage. The main objective of this method is to ensure that the device current follows a constant reference. The proposed algorithm has improved adaptability and applicability. In this method, the operating temperature is assumed to be constant. However, the value of this parameter varies. In order to address this point, a constant temperature precharging algorithm is proposed in this thesis. The proposed control strategy regulates the junction temperature of the semiconductor device. This parameter is controlled in such a way that the thermal stress on the semiconductor device is low. The proposed precharging algorithms are verified on a laboratory prototype. The experimental results obtained using this setup, are presented in this thesis. Another important consideration is that SSPCs/ SSCBs have high on state power loss. This is because semiconductor devices are in the load current path. To overcome this limitation, silicon controlled rectifier (SCR) based SSPCs/ SSCBs are considered as one of the promising solutions. The second part of the contribution of the thesis is focused on SCR based SSPCs/ SSCBs. Z Source Breakers (ZSBs) are one class of SCR based SSPCs/ SSCBs. A coupled inductor based bidirectional ZSB topology is proposed in this thesis. The proposed topology has lower on state power loss, and simple structure. However, ZSBs imposes an upper limit on the step-load change, and this complicates the design of protection coordination. In order to address these points, an SCR-based bidirectional SSPC/ SSCB (SCR-BCB) topology is proposed in this thesis. Additionally, the proposed SCR-BCB topology has soft reclosing capability. The proposed SCR-BCB topology is verified using simulation and hardware experiments.